Pengaruh Variabel Internal terhadap Nilai Perusahaan pada Industri Perbankan - Ariashinta, Dewanti; Budiarti, Laeli (Jurnal Riset Akuntansi Soedirman, 2025)
This study aims to analyze and obtain empirical evidence of internal variable that consist of the Good Corporate Governance, credit risk, capital structure and company size as control variables on company value. The theory tested in this study is signal theory. This study uses quantitative methods taken from annual report data from banking companies listed on the Indonesia Stock Exchange for the period 2020-2022. By using a purposive sampling technique produces 114 data. Company value is measured by Price to Book Value (PBV), Good Corporate Governance refers to the GCG self-assessment composite rating, credit risk is measured using Non-Performing Loans (NPL), capital structure is measured using Debt to Equity Ratio (DER), and company size is measured using the natural log of total assets. Data is processed using eviews 12. The data analysis model uses a random effect model. The results show that GCG, credit risk, capital structure have a positive effect on company value and the results do not change if tested with or without the control variable company size.